2009
DOI: 10.1097/jom.0b013e3181bae17c
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Central Auditory Dysfunction Induced by Occupational Exposure to Organic Solvents

Abstract: Occupational exposure to solvents may induce both peripheral and central auditory dysfunction. The dichotic digits test seems as a sensible tool to detect central auditory dysfunction associated with solvent exposure. Hearing loss prevention programs may use this tool to monitor hearing in solvent-exposed workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
5
38
1
12
Order By: Relevance
“…The authors suggest the possibility that the data were underestimated, since the methods used may have failed to detect auditory disorders due to their locations in the auditory system. Workers exposed to combined "noise and solvent mixture," when compared with non-exposed controls, had worse results in CAP tests: Speechin-Silence (SS), PPS 36 , HINT 36,39 , Random Gap Detection (RGD) 36,37,39 and DD 34,36 , but no statistically significant difference was observed for MLD 36 . The results suggest that solvents may be adversely associated with central auditory dysfunction.…”
Section: Low Exposure To Mixturementioning
confidence: 94%
See 4 more Smart Citations
“…The authors suggest the possibility that the data were underestimated, since the methods used may have failed to detect auditory disorders due to their locations in the auditory system. Workers exposed to combined "noise and solvent mixture," when compared with non-exposed controls, had worse results in CAP tests: Speechin-Silence (SS), PPS 36 , HINT 36,39 , Random Gap Detection (RGD) 36,37,39 and DD 34,36 , but no statistically significant difference was observed for MLD 36 . The results suggest that solvents may be adversely associated with central auditory dysfunction.…”
Section: Low Exposure To Mixturementioning
confidence: 94%
“…In all studies of possible impairment to CANS and listening skills, the results suggested action of solvents on the central auditory pathways, indicating that PTA might not be the only recommended audiological test for this population 17,34,36,37,39 .…”
Section: Low Exposure To Mixturementioning
confidence: 99%
See 3 more Smart Citations